Recetario multimedia usando técnicas de interacción natural - Sandoval Vicuña, Alejandra (Universidad de San Buenaventura - Cali, 2016)
This project aims to propose a more efficient and interactive alternative to accompany the user when cooking, enriching the user experience using the features that a mobile technology can provide.